Respostas
respondido por:
2
2. (x-3)=5. (x+2)-1
2x-6=5x+10-1
2x-5x=10-1-6
-3x=3
x= 3/-3
x= -1
Qualquer dúvida só comentar.
Espero ter ajudado :)
2x-6=5x+10-1
2x-5x=10-1-6
-3x=3
x= 3/-3
x= -1
Qualquer dúvida só comentar.
Espero ter ajudado :)
VinnyAkame:
Não seria +6
respondido por:
10
Resolução
2.(x - 3) = 5.(x + 2) - 1
2x - 6 = 5x + 10 - 1
2x - 5x = 10 - 1 + 6
- 3x = 15 .(-1)
3x = - 15
x = - 15
3
x = - 5
2.(x - 3) = 5.(x + 2) - 1
2x - 6 = 5x + 10 - 1
2x - 5x = 10 - 1 + 6
- 3x = 15 .(-1)
3x = - 15
x = - 15
3
x = - 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás